Long-term outcomes after myocardial infarction in middle-aged and older patients with congenital heart disease—a nationwide study. (21st November 2020) - Fedchenko, Maria; Mandalenakis, Zacharias; Giang, Kok Wai; Rosengren, Annika; Eriksson, Peter; Dellborg, Mikael
Abstract: Aims : We aimed to describe the risk of myocardial infarction (MI) in middle-aged and older patients with congenital heart disease (ACHD) and to evaluate the long-term outcomes after index MI in patients with ACHD compared with controls. Methods and results : A search of the Swedish National Patient Register identified 17 189 patients with ACHD (52.2% male) and 180 131 age- and sex-matched controls randomly selected from the general population who were born from 1930 to 1970 and were alive at 40 years of age; all followed up until December 2017 (mean follow-up 23.2 ± 11.0 years). Patients with ACHD had a 1.6-fold higher risk of MI compared with controls [hazard ratio (HR) 1.6, 95% confidence interval (CI) 1.5–1.7, P  < 0.001] and the cumulative incidence of MI by 65 years of age was 7.4% in patients with ACHD vs. 4.4% in controls. Patients with ACHD had a 1.4-fold increased risk of experiencing a composite event after the index MI compared with controls (HR 1.4, 95% CI 1.3–1.6, P  < 0.001), driven largely by the occurrence of new-onset heart failure in 42.2% ( n  = 537) of patients with ACHD vs. 29.5% ( n  = 2526) of controls. Conclusion : Patients with ACHD had an increased risk of developing MI and of recurrent MI, new-onset heart failure, or death after the index MI, compared with controls, mainly because of a higher incidence of newly diagnosed heart failure in patients with ACHD. Recognizing and managing the modifiable cardiovascular risk factors should be of importance to reduce morbidity and mortality in patients with ACHD. Graphical Abstract: